From Everyman to Hamlet: A Distant Reading. - Brljak, Vladimir (Renaissance Studies, 2026)
The sixteenth century sees English drama move from Everyman to Hamlet: from religious to secular subject matter and from personified abstractions to characters bearing proper names. Most modern scholarship has explained this transformation in terms originating in the work of Jacob Burckhardt: concern with religion and a taste for personification are deeply seated facets of 'medieval' mentality, discarded with the advent of the secularism and individualism in the 'Renaissance' or 'early modern' period. The article presents a different account of the shift, based on a 'distant reading' of a select corpus of English drama from 1531 to 1600, drawn from Martin Wiggins's British Drama, 1533–1642: A Catalogue. This reading shows that the decline of overtly religious subject matter was due not to secularization but rather suppression through increasingly effective regulation and censorship, while the decline of personification is plausibly ascribed to the consolidation of a genuinely commercial and popular theatrical scene in 1570s London. So understood, these developments have important implications for the history of English drama as well as of personification and personification‐allegory more broadly, within and beyond the English tradition.